Prophetic developments with particular reference to the early Brethren movement - Coad, F. Roy, 1925-; Christian Brethren Research Fellowship (UK) (Middlesex, UK C.B.R.F., 1966)
Includes bibliographical references.
Brethren writer.
Keywords: Eschatology -- Brethren movement